Genetic and morphological variation in an ecosystem engineer, Lithophyllum byssoides (Corallinales, Rhodophyta). Issue 1 (30th November 2016) - Pezzolesi, Laura; Falace, Annalisa; Kaleb, Sara; Hernandez‐Kantun, Jazmin J.; Cerrano, Carlo; Rindi, Fabio
Abstract : Lithophyllum byssoides is a common coralline alga in the intertidal zone of Mediterranean coasts, where it produces biogenic concretions housing a high algal and invertebrate biodiversity. This species is an ecosystem engineer and is considered a target for conservation efforts, but designing effective conservation strategies currently is impossible due to lack of information about its population structure. The morphological and molecular variation of L. byssoides was investigated using morphoanatomy and DNA sequences ( psb A and cox 2, 3) obtained from populations at 15 localities on the Italian and Croatian coasts. Lithophyllum byssoides exhibited a high number of haplotypes (31 psb A haplotypes and 24 cox 2, 3 haplotypes) in the central Mediterranean. The psb A and cox 2, 3 phylogenies were congruent and showed seven lineages. For most of these clades, the distribution was limited to one or a few localities, but one of them (clade 7) was widespread across the central Mediterranean, spanning the main biogeographic boundaries recognized in this area. The central Mediterranean populations formed a lineage separate from Atlantic samples; psb A pair‐wise divergences suggested that recognition of Atlantic and Mediterranean L. byssoides as different species may be appropriate. The central Mediterranean haplotype patterns of L. byssoides were interpreted as resulting from past climatic events in the hydrogeological history of the Mediterranean Sea. The high haplotype diversity and the restricted spatial distribution of the seven lineages suggest that individual populations should be managed as independent units.